Economic Growth, Inequality, and Poverty : Findings from a New Data Set - Adams, Richard H., Jr. (World Bank, Washington, DC, 2014)
The author uses new data from 50 developing countries and 101 intervals to examine the impact of economic growth on poverty and inequality. He finds that growth represents an important means for reducing poverty in the developing world. When economic growth is measured by survey mean income (consumption), there is a strong, statistical link between growth and poverty reduction. When economic growth is measured by GDP per capita, the statistical relationship between growth and poverty reduction is still present, albeit not quite as strong. Economic growth reduces poverty because growth has little impact on income inequality. In the data set income inequality rises on average less than 1.0 percent a year. Since income distributions are relatively stable over time, economic growth tends to raise incomes for all members of society, including the poor. When growth is measured by survey mean income (consumption), the elasticity of poverty with respect to growth is -2.59. In other words, on average, a 10 percentage point increase in economic growth (measured by survey mean income) will produce a 25.9 percent decrease in the proportion of people living in poverty ($1 a person a day).